1981
DOI: 10.1039/an9810601125
|View full text |Cite
|
Sign up to set email alerts
|

Communication. Flow injection sample introduction for atomic-absorption spectrometry: applications of a simplified model for dispersion

Abstract: COMMUNICATION 1125 CommunicationMaterial for publication as a Communication must be on an urgent matter and be of obvious scienti$c importance. Rapidity of publication is enhanced if diagrams are omitted, but tables and formulae can be included. Communications should not be simple claims for priority: this facility for rapid publication is intended for brief descriptions of work that has progressed to a stage at which it is likely to be valuable to workers faced with similar problems. A fuller paper may be off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…features of using flow injection as a sample introduction system and suggested that solvent extraction could be carried out in the flowing stream. Tyson and Idris [12,13] have discussed the characteristics of the instrument response curve and'demonstrated the feasibility of the flow injection analogue of the standard addition method; they proposed the use of a concentration gradient.generate � ·by flow injection as the basis of a single-standard calibration method. Greenfield [14] has demonstrated that these ideas are also workable with an inductively-coupled plasma instrument whose use has also been described by Jacintha et al [15].…”
mentioning
confidence: 99%
“…features of using flow injection as a sample introduction system and suggested that solvent extraction could be carried out in the flowing stream. Tyson and Idris [12,13] have discussed the characteristics of the instrument response curve and'demonstrated the feasibility of the flow injection analogue of the standard addition method; they proposed the use of a concentration gradient.generate � ·by flow injection as the basis of a single-standard calibration method. Greenfield [14] has demonstrated that these ideas are also workable with an inductively-coupled plasma instrument whose use has also been described by Jacintha et al [15].…”
mentioning
confidence: 99%
“…The effect of varying the dispersion has already been described for the interference of phosphate on calcium. 5 If the required minimum ratio of interferent to analyte species, RiIa, is known, the relationship between concentration of interferent, sample concentration, Cx, and standard concentration, Cs, may be readily calculated from equations (1)-(3) above,6 bearing in mind that the analyte concentration at the peak is made up of contributions from carrier stream and injected solution, as follows :…”
Section: Fi Standard Additions Methodsmentioning
confidence: 99%
“…The basis of the single, well-stirred tank model, in which all dispersion ef fects are considered to be due to plug flow into a tank with only one inlet and outlet, and the concentration is detected at the outflow with no further disper sion, has been described in detail [ 86]; the equations for the rise curve, peak maximum, fall curve and peak width have been derived [87].…”
Section: Peak Areamentioning
confidence: 99%